Cerebro- and renoprotective activities through platelet-derived biomaterials against cerebrorenal syndrome in rat model. (September 2019) - Yip, Hon-Kan; Chen, Kuan-Hung; Dubey, Navneet Kumar; Sun, Cheuk-Kwan; Deng, Yue-Hua; Su, Chun-Wei; Lo, Wen-Cheng; Cheng, Hsin-Chung; Deng, Win-Ping
Abstract: Though the cross-induction of either acute kidney (AKI) injury to ischemic stroke (IS) or IS to AKI might not be encountered in the early stages of cerebrorenal syndrome (CRS), both pathologies coexist in late stages. Therefore, we firstly established a late stage CRS rat model by simultaneous induction of both diseases, and further, cerebro and reno-protective activities of human platelet-rich plasma (hPRP), a blood-derived tissue engineering biomaterial, were tested in this pathology. hPRP was administrated via left common carotid artery and abdominal aorta 2 h post-sham procedure in Sprague-Dawley rats. Circulatory inflammatory markers (TNF-α/MPO/IL-6/Ly6G/CD11b/c), histopathologic cerebro and renal changes and oxidative stress were determined. Inflammation, infarct size, brain-associated inflammatory/DNA and mitochondrial damage and oxidative-stress with reduced neurons and neurological function were manifested in CRS group compared to other groups. CRS group also demonstrated declined renal function, accelerated renal collagen deposition, fibrosis and compromised glomerular podocyte components (podocin/ZO-1/fibronectin/synaptopodin). However, hPRP simultaneously suppressed all the inflammatory, cerebral and renal pathologic characteristics. hPRP also inhibited the expression of brain-associated inflammatory/DNA/mitochondrial damage and oxidative-stress biomarkers. These findings imply that hPRP may effectively exert cerebro- and renoprotective activities in late stage CRS through anti-oxidative, anti-inflammatory, anti -DNA and anti -mitochochondrial damaging activities.